Pengaruh Perceived Value dan Emotional Attachment Serta Word of Mouth terhadap Loyalitas Pelanggan Fore Coffee di Kecamatan Medan Baru - Annisa Dwi Febrianti; Ihsan Effendi; Nur Aisyah (Jurnal Manajemen Kreatif dan Inovasi, 2026)
This study examines the influence of perceived value, emotional attachment, and word of mouth on Fore Coffee customer loyalty in Medan Baru District. A quantitative research approach with a survey method was employed. Data were collected through Google Forms distributed to eligible Fore Coffee customers, while respondents' perceptions were measured using a Likert scale. A total of 180 respondents were selected through purposive sampling. The collected data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique with SmartPLS software. The findings reveal that perceived value, emotional attachment, and word of mouth each have a positive and significant effect on customer loyalty. Furthermore, these three variables simultaneously contribute to strengthening customer loyalty toward Fore Coffee in Medan Baru District. Reliability testing also indicates that all constructs satisfy the recommended criteria, with Composite Reliability values exceeding 0.70 and Cronbach's Alpha values above 0.60. Therefore, the research instrument is considered reliable, and the proposed model is appropriate for explaining customer loyalty in the context of this study.